Сто років книзі «За македонцките работи» - Ристовський, Б. (Народна творчість та етнографія, 2009)
The hundred-year-old volume, Krste Petkov Misirkov's On «Macedonian Matters», marks a fundamental date in contemporary Macedonian history. It is a mature, scientific and scholarly elaboration and a wise national political refining of Macedonian national thinking in all its growth to that date. It is also a phenomenon, a historical threshold in the process of Macedonian national and cultural and state affirmation. Among the Macedonian scientific and scholarly public – but also in the wider public – Misirkov's volume has been mainly treated from the aspect of its incontestable place and role in the history of the codification of the contemporary Macedonian literary language. If it were only this, Misirkov would still have secured for himself a worthy, prominent place among the leading figures in Macedonian national thought and activity. The broader scientific and scholarly historical and national political components in this volume are, however, not infrequently overlooked and, even here in Macedonia, problematicised. This was, in effect, the only book that gave an objective historical synthesis of the past, and particularly of the then contemporary present of Macedonia and the Macedonians. Misirkov was directly involved in the liberation movement and assembled the first well-argumented and objective critical assessment of the programme and practical actions of the Macedonian revolutionary organisation, while at the same time he was alsothe first authentic reviewer of the Ilinden Uprising as an expression of the spirit of the people, as an all-inclusive and decisive popular undertaking leading to Macedonian liberation and a Macedonian state. «On Macedonian Matters» thus testifies to the centuries-old basis of Macedonian scholarly and scientific historiography and, with its multifarious reflections, it preserves the relevance of this reality in contemporary Macedonia.